Catalytic methane decomposition to hydrogen and carbon over hydrotalcite‐derivative composition‐uniform and sintering‐resistant Ni‐Fe/Al2O3 alloy catalysts. (11th August 2022) - Wang, Peng; Zhu, Hong; Huang, Min; Wan, Chunsheng; Li, Dalin; Jiang, Lilong
Summary: Ni‐Fe/Al2 O3 alloy catalysts obtained from Ni3‐ x Fe x Al ( x  = 0‐1.2) hydrotalcite‐like compounds are tested in CH4 decomposition at 600°C to produce H2 and carbon. By calcination at 500°C, nickel‐iron‐aluminum hydrotalcite is decomposed into Ni(Fe, Al)O solid solution; upon reduction at 800°C, Ni‐Fe alloy with uniform composition and the average size of 9.4 to 10.3 nm is formed. The Ni‐Fe/Al2 O3 alloy catalysts exhibit higher catalytic life and carbon yield than the Ni3 Al counterpart, with the optimal alloy composition being Ni: Fe = 4:1. Carbon nanotubes are produced on all catalysts, and the average carbon diameter is decreased to a certain degree by Ni‐Fe alloying. XRD indicates that Ni‐Fe alloy is less sintered than Ni metal under the reaction atmosphere, which may account for the decrease in the carbon diameter. This study provides a way for the preparation of a uniform Ni‐Fe alloy catalyst and its sintering resistance is helpful for controlling the carbon morphology. Abstract : Ni‐Fe‐Al hydrotalcite‐like compounds are a good precursor for the preparation of Ni‐Fe alloy catalysts. Upon calcination and reduction, Ni‐Fe‐Al HTlcs are transferred to Ni(Fe, Al)O solid solution and the homogeneously mixed nickel and iron species are co‐reduced to yield composition‐uniform and well‐dispersed alloy particles. The Ni‐Fe/Al2O3 alloy catalysts exhibit higher carbon yield in methane decomposition than the Fe‐free Ni counterpart, with the optimal composition being Ni:Fe = 4:1. Moreover, Ni‐Fe alloying enhances the sintering resistance, leading to a decrease in the carbon diameter.